The Relationship of Interferon Gamma +874T/A and Interleukin-10 -1082G/A Gene Polymorphism to The Recovery of Multidrug Resistant Tuberculosis Patients - Ita Haryatie; Harsini Harsini; Reviono Reviono (Jurnal Respirologi Indonesia, 2017)
Background: Multidrug resistant (MDR) TB caused by the M.Tb strain is resistant toward at least rifampicin and isoniazid. Interferon Gamma is responsible for activating macrophages and phagocytosis for M.Tb destruction. Interleukin 10 causes a significant decrease in reactive nitrogen intermediates, increased arginase 1, and overall decreased macrophage function. Gene mutation causes IFN production by CD4 - T cells less effective and disrupts the immune response against M.Tb. There has been no research on the relationship between IFN-γ and IL-10 gene polymorphisms with TB recovery in Indonesia, especially in patients with MDR-TB. The aim of this study is to determine gene polymorphism relationship of IFN-γ +874T/A and IL-10 -1082G/A with MDR-TB recovery. Methods: This study was a non-experimental clinical trial with a retrospective cohort design. The study was conducted on 105 MDR-TB patients treated in dr. Moewardi Hospital between January 2011-June 2014 consists of 84 recovered patients and 21 patients died/failed. Results: Gene polymorphism of IFN-γ +874T/A was obtained OR=0.703 (0.265-1.863) and P=0.477 which mean IFN-γ +874 T/A gene was not related to recovered case of MDR-TB. The IL-10 -1082G/A gene obtained the value of OR=0.657 (0.173-2.491) and the value P=0.785 which means that IL-10 -1082G/A is not related to the MDR-TB case recovery. Conclusions: There is no relationship of IFN-γ + 874T/A and IL-10 -1082G/A gene polymorphisms in the recovery of MDR-TB patients. (J Respir Indo. 2017; 37(4): 299-306)